ЄМНІСНИЙ СЕНСОР З СИСТЕМОЮ ПАРАЛЕЛЬНИХ КОМПЛАНАРНИХ ЕЛЕКТРОДІВ ДЛЯ ВИМІРЮВАННЯ ПОВІТРЯНОГО ЗАЗОРУ В ГІДРОГЕНЕРАТОРАХ - Левицький, А.С.; Рассовський, В.Л.; Зайцев, Є.О. (Інститут електродинаміки НАН України, Київ, 2023)
A capacitive sensor for measuring the air gap between the boring of the stator core and the poles of the rotor in a powerful hydrogenerator is proposed and investigated. The sensor consists of a system of equal in width tape parallel coplanar high-potential and low-potential electrodes, between which grounded electrodes are placed. The ratios between the width of the high-potential, low-potential and grounded electrodes are selected depending on the size of the nominal gap. The electrodes are formed on a dielectric substrate mounted on the boring of the stator core. To reduce the effect of edge effects on the short sides of high-potential electrodes, the length of the low-potential electrodes is chosen to be smaller than the length of the high-potential electrodes by a value determined by the nominal gap. It is proposed to place all electrodes along the length perpendicular to the boring core generatrix to reduce the measurement error due to the influence of the rotor pole curvature. The electrical capacitance between the system of high-potential electrodes connected in parallel and the system of low-potential electrodes connected in parallel, which functionally depends on the size of the air gap, is measured. Analytical and graphical dependences for the sensor conversion function intended for use on a SGK538 / 160-70M bulb hydrogenerator have been determined. The value of the error caused by the curvature of the rotor poles in this hydrogen generator was calculated. The sensor in comparison with analogs has higher accuracy of measurement. The sensor or sensor system can be used as a stand-alone device or as part of monitoring and diagnostic systems. References 19, figures 6.